Maqashid Syariah in the Companions and Tabi'in Period - Muhammad Afifuddin; Mahdum Zahid (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Maqashid Syariah, or the objectives of Islamic law, is an important concept in understanding Islamic law that focuses on achieving good and preventing harm. In the period of the Companions and Tabi'in, this maqashid became the basis for legal decision-making and religious practices. This study aims to analyze how the Companions and Tabi'in implemented maqashid sharia in the social, political, and economic contexts of their time. Meanwhile, the research method used in this journal is library research. The findings show that the Companions and Tabi'in did not only focus on legal texts, but also considered the social impact of legal decisions, thus creating justice and social welfare.